Interdependence Between Green Economic Growth And Digital Transformation In Indonesia - Afini Febriani Laili; Rusiadi Rusiadi; Lia Nazliana Nasution; Bhaktiar Efendi; Suhendi Suhendi (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study investigates the effectiveness of policy controls on digital-based green economy indicators in Indonesia using the Forecast Error Variance Decomposition (FEVD) approach. The analysis centers on variables such as Employed Person, Green Credit, Exports of ICT Goods, Household Debt to GDP, Green Consumption, Green Trade, and Green Sustainable Development. The findings reveal that in the short term, most variables are predominantly influenced by their own past values, especially the Employed Person indicator. However, in the medium and long term, the interaction between Household Debt to GDP and other variables emerges as a pivotal factor in reinforcing sustainable development policies. This suggests that household financial stability plays a vital role in supporting green consumption, digital exports, and sustainability financing. These results align with previous studies highlighting the interconnected roles of labor, household finance, and green trade in driving inclusive green economic growth. Accordingly, development strategies should be tailored based on temporal horizons and the structural interlinkages among key variables. This research contributes empirically to the formulation of adaptive, digital-driven green policy frameworks in the post-pandemic era.